Propuesta educativa para prevenir la desnutrición crónica infantil en menores de 5 años. - García Pastrana, Cindy Carolina (2025)
Malnutrition is one of the leading causes of death in children under 5 years of age and one of the most common factors that threaten the life and health of the child population around the world. In this context, the study's general objective was to design an information booklet to prevent chronic malnutrition in children under 5. The research required a methodology with a non-experimental quantitative cross-sectional approach using documentary research. The study used a quantitative approach with a sample of 50 articles. The researcher obtained six topics by synthesizing the articles of this literature review that address the main strategies and interventions to prevent childhood malnutrition: nutritional education, nutritional supplementation, integrated interventions for access to water, sanitation, and hygiene (WASH), dietary diversity, economic interventions, and complementary feeding. The systematic review results allowed the development of an educational proposal based on an information booklet through ICT to prevent childhood malnutrition. The information booklet developed contains information on the six strategies found in the literature that can be useful for counseling families with children under 5 years of age by health professionals for health promotion and prevention tasks.